Potentially toxic Pseudo-nitzschia species in plankton and fecal samples of Eubalaena australis from Península Valdés calving ground, Argentina - D'agostino, Valeria Carina; Hoffmeyer, Monica Susana; Almandoz, Gaston Osvaldo; Sastre, Viviana; Degrati, Mariana (Journal of Sea Research)
Península Valdés (PV) in Argentina is an important calving ground for the southern right whale Eubalaena australis. However, a high mortality of calves has been observed in the last years, which could be associated with phycotoxin exposure. During a sampling program conducted late in the calving seasons of 2004, 2005 and 2010, potentially toxic species of the genus Pseudo-nitzschia were observed to be an important component of the phytoplankton community and they were also found in fecal samples of two live whales and three stranded whales. In line with this, in the present study Pseudo-nitzschia australis, Pseudo-nitzschia fraudulenta, Pseudo-nitzschia pungens and the complex Pseudo-nitzschia pseudodelicatissima were identified in fecal samples and phytoplankton samples by light and electron microscopy. Although no toxin analysis was carried out in the present study, our findings suggest that E. australis could be exposed to domoic acid in their calving ground. Fil: D'agostino, Valeria Carina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina Fil: Hoffmeyer, Monica Susana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto Argentino de Oceanografía. Universidad Nacional del Sur. Instituto Argentino de Oceanografía; Argentina. Universidad Tecnológica Nacional. Facultad Regional Bahía Blanca; Argentina Fil: Almandoz, Gaston Osvaldo. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Sastre, Viviana. Universidad Nacional de la Patagonia Argentina Fil: Degrati, Mariana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina. Universidad Nacional de la Patagonia. Facultad de Ciencias Naturales. Sede Puerto Madryn; Argentina